Children of Communism: Former Party Membership and the Demand for Redistribution. Issue 3 (4th May 2023) - Libman, Alexander; Popova, Olga
ABSTRACT: The paper looks at the persistence of egalitarian norms in post-Communist societies by focusing on the former members of the Communist parties in Central and Eastern Europe (CEE) and Russia and their children. Using individual-level survey data, we distinguish between Russia and the CEE countries in this respect. While in the CEE there is some evidence that both former members of the Communist parties and their children have stronger preferences for redistribution than the rest of the population (the results for the children are more significant), in Russia, only children of Communists (but not Communists themselves) support redistribution.